Oral Iron Supplementation in Pregnancy: Current Recommendations and Evidence-Based Medicine Suplementação oral de ferro na gravidez: recomendações atuais e medicina baseada na evidência - Ana Filipa Moreira Duarte; Ana Catarina Simões Viana Carneiro; Ana Teresa Barbosa Maciel Meira Peixoto; Daniela Filipa Pereira Montenegro; Débora Sofia Carvalho Campos; Ana Patrícia Ribeiro Alves; Ana Rita Mota Magalhães Costa; Andreia Patrícia Machado Fino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To review the evidence about universal iron supplementation in pregnancy to prevent maternal anemia. Methods Bibliographic research of randomized and controlled clinical trials, meta-analyses, systematic reviews, and clinical guidelines, published between August 2009 and August 2019, using the MeSH terms: iron; therapeutic use; pregnancy; anemia, prevention and control. Results We included six clinical guidelines, three meta-analyses and one randomized controlled clinical trial. Discussion Most articles point to the improvement of hematological parameters and reduction of maternal anemia risk, with supplementary iron. However, they do not correlate this improvement in pregnant women without previous anemia with the eventual improvement of clinical parameters. Conclusion Universal iron supplementation in pregnancy is controversial, so we attribute a SORT C recommendation strength.